Country Size, Currency Unions, and International Asset Returns - Tarek A. Hassan (Oesterreichische Nationalbank (OeNB), 2009)
The fact that economies differ in size has important implications for international asset returns. I solve for the spread on international bonds and stocks in an endowment economy with complete asset markets and non-traded goods. The model predicts that larger countries have lower real interest rates because their bonds provide insurance against shocks that affect a larger fraction of the world economy. Larger countries' bonds must therefore pay lower excess returns in equilibrium and uncovered interest parity fails. By a similar logic, stocks in the non-traded sector of larger countries also tend to pay lower excess returns. If asset markets are segmented, the introduction of a currency union lowers real interest rates and expected returns on stocks in the non-traded sector of participating countries. I test the predictions of the model for a panel of OECD countries and show that they are strongly supported by the data: Investors earn lower excess returns on bonds and stocks in the non-traded sector of larger countries. Similarly, excess returns on EMU member countries'bonds and stocks in the non-traded sector fell after European monetary integration.
Keywords: F3; G0; 330; International return differentials; country size; currency unions; uncovered interest parity; market segmentation